Perancangan Rombong Multifungsi untuk Pedagang Kaki Lima - Venta Clariza Exstrilia; Grace Mulyono; Frenky Tanaya (Intra, 2018)
— People lifestyle interested street food is increasing. This can give innovation to the food cart development by providing functions such as tables and chairs that become united with the food cart. In addition, food cart can also be used indoors or outdoors. "Multifunction Food Cart Design for Street Food Sellers" is a universal design so it can be used by anyone who wants to sell food. The design concept of "Form Follows Function" is a design architects, Frank Lloyd Wright. This ideology refers to the design of a design-based element that has decorative function and also contains benefits that can be felt by the food sellers, namely the availability of facilities such as tables and chairs for buyers with a single package system and knockdown system. So the food cart is worth to attract the attention of buyers by giving a touch of uniqueness, lightweight, universal, one package, all in one, and moveable.